Investigation of the Thermal Sensitive Spectral Response of Chalcogenide Fiber Bragg Grating - Eliska Jurisova; Libor Ladanyi; Jarmila Mullerova (Communications - Scientific letters of the University of Zilina, 2013)
This contribution presents numerical studies of the nonlinear fiber Bragg grating (FBG). The proposed model corresponds well to chalcogenide FBG as a considerable tool for optical switching. The spectral response of this device is discussed theoretically. Simulations based on the nonlinear coupled mode theory are used for investigating the relationships between the spectral transmission of nonlinear chalcogenide FBG and the grating parameters. The influence of the temperature dependence of FBG is numerically investigated. Numerical results show that the ambient temperature has an influence on the spectral response of FBG. The results are indications for applications in optical switches for all-optical communication networks and this can be important for wavelength division multiplexing optical networks.